GC-MS – Still standing for clinical and forensic analysis: validation of a multidrug method to detect and quantify illicit drugs - Ferreira, Ana Beatriz; Castro, André Lobo; Tarelho, Sónia; Rodrigues, Pedro; Franco, João Miguel (Taylor & Francis, 2021)
An SPE-GC-MS analytical method using whole blood samples has been developed and validated to detect and quantify nineteen compounds belonging to the Drugs of Abuse (DA) groups of cocaine and metabolites, opiates and new psychoactive substances (NPS). The method detailed here is necessary because the recreational consumption of these DA has increased considerably in recent years and poly-drug-consumption is now very common. The method developed was both specific and selective. Three different working ranges have been defined due to the differences between therapeutic, toxic and lethal concentrations of DA. Linearity was confirmed for the defined working ranges of all DA, except pseudoephedrine, ephedrine, norephedrine, and TFMPP. Since the remaining nineteen substances showed heteroscedasticity, six ponderation factors were studied to find the best fit for each compound. Limits of Detection and Lower Limits of Quantification have been studied and defined. No carryover was noted, with acceptable extraction recoveries. The achievement of all validation criteria according to international guidelines allows the application of the proposed method in routine forensic analysis. Using this method can also significantly reduce response times and GC-MS analysis costs.
Keywords: Forensic Toxicology; multi-drug method; Cocaine; Opiates; New psychoactive substances; GC-MS; Solid-Phase Extraction